1978
DOI: 10.1002/app.1978.070220315
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and physical properties of poly(butylene terephthalate)

Abstract: SynopsisLiquid nitrogen-quenched PBT samples produce much larger spherulites of an optic axis orientation different from that of the air-cooled samples. Optical and scanning electron microscopy show that glass fibers in the glass-reinforced PBT sample nucleate the growth of well-defined spherulites along the glass fiber axis. Fracture studies at temperatures below and above the T, indicate, respectively, brittle and ductile interspherulite boundary fracture. From dynamic mechanical studies, three transitions d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…These diffraction pattern reportedly correspond to triclinic unit cell structure. It has also been reported that the solution cast PBT exhibits spherulitic morphology [17]. In comparison, PB-4-HB did not show strong and distinct diffraction patterns similar to that of PBT in the range 10°to 20°in accordance with its relatively weaker semi-crystalline nature.…”
Section: Morphology Of Pb-4-hbmentioning
confidence: 68%
See 1 more Smart Citation
“…These diffraction pattern reportedly correspond to triclinic unit cell structure. It has also been reported that the solution cast PBT exhibits spherulitic morphology [17]. In comparison, PB-4-HB did not show strong and distinct diffraction patterns similar to that of PBT in the range 10°to 20°in accordance with its relatively weaker semi-crystalline nature.…”
Section: Morphology Of Pb-4-hbmentioning
confidence: 68%
“…In the WAXRD analysis UPEE 1 showed a halo pattern typical of amorphous polymers and the PB-4-HB showed WAXRD pattern typical of semi-crystalline polymers. In the WAXRD analysis, PBT has been reported to show strong diffraction peaks at 2θ016.0°, 17.3°, 20.6°, 23.4°and 25.2° [17]. These diffraction pattern reportedly correspond to triclinic unit cell structure.…”
Section: Morphology Of Pb-4-hbmentioning
confidence: 96%
“…An analogous situation has been observed for many polyesters, among which a well-known example is represented by poly(butylene terephthalate). [26] As far as the overall kinetic constant k n is concerned, two distinct trends with T c can be observed (see Figure 11), each of them being relative to one of the two crystalline phases.…”
Section: Resultsmentioning
confidence: 98%
“…PET, PBT and polycarbonate are polyesters of similar chemical structure in that their repeat units each contain carbonyl groups and phenyl rings in comparatively close proximity. Many workers (see, for example, refs 17, 29–33) attribute the β‐absorptions to carbonyl‐driven localized motions of carbonyl and phenyl groups. The localized nature of these motions is indicated by the observation that the shape and location of the β loss peak in PET is unaffected by crystallinity.…”
Section: Resultsmentioning
confidence: 99%